OUT COME OF TRIAL OF SCAR IN PATIENTS WITH PREVIOUS CAESAREAN SECTION - Khan, Bushra; Deeba, Farhat; Bashir, Rubina; Khan, Wajiha (Journal of Ayub Medical College Abbottabad, 2014)
Background: Patients who had one caesarean section were previously not given a trial of scar due to fear of increased morbidity. However, recently there has been a trend to give a trial of labour to patients with a previous caesarean section for a non-recurrent cause. Medical evidence indicates that 60-80% of women can achieve vaginal delivery after a previous lower segment caesarean section. Proper selection of patients for trial of scar and vigilant monitoring during labour will achieve successful maternal and perinatal outcome. The objective of our study is to establish the fact that vaginal delivery after one caesarean section has a high success rate in patients with previous one caesarean section for non-recurrent cause. Methods: The study was conducted in Ayub Teaching Abbottabad, Gynae-B Unit. All labouring patients, during the study period of five years, with previous one caesarean section and between 37 weeks to 41 weeks of gestation for a non-recurrent cause were included in the study. Data was recorded on special pro forma designed for the purpose. Patients who had previous classical caesarean section, more than one caesarean section, and previous caesarean section with severe wound infection, transverse lie and placenta previa in present pregnancy were excluded. Foetal macrosomia (wt>4 kg) and severe IUGR with compromised blood flow on Doppler in present pregnancy were also not considered suitable for the study. Patients who had any absolute contraindication for vaginal delivery were also excluded. Results: There were 12505 deliveries during the study period. Total vaginal deliveries were 8790 and total caesarean sections were 3715. Caesarean section rate was 29.7%. Out of these 8790 patients, 764 patients were given a trial of scar and 535 patients delivered successfully vaginally (70%). Women who presented with spontaneous onset of labour were more likely to deliver vaginally (74.8%) as compared to induction group (27.1%). Conclusion: Trial of vaginal birth after caesarean (VBAC) in selected cases has great importance in the present era of the rising rate of primary caesarean section. Keywords: caesarean section; vaginal birth after caesarean section